Design of Flow Control System with A Kickback Flow as A Manipulated Variable - Yulius Deddy Hermawan (Eksergi, 2017)
The open loop experiment of water flow dynamic in pipe has been done in laboratory. Pump was used to flow water in pipe. Part of liquid from discard of pump was recycled back to the suction of pump (kickback) and adjusted to control the liquid flow to the next process. The open loop laboratory experiment produced the steady state parameters; they were discard flowrate =16.6 [L/min], kickback flowrate =5.8 [L/min], and liquid flowrate to the next process =10.8 [L/min]. These steady state parameters were then used as the initial value for closed loop simulation with computer programming. This study has proposed the liquid flow control configuration by manipulating the kickback flow. Proportional Integral (PI) was proposed to control the flow and Routh-Hurwitz (RH) stability criterion was chosen to predict the range of the controller gain (Kc) that gives stable response. The closed loop model was solved analytically with Laplace method for both servo and regulatory problems. The set point change of flow and disturbance were made based on step function. The scilab software was used to do closed loop simulation. Based on RH stability criterion, the controller gain should be negative in order to give stable response. The closed loop simulation showed that by using controller gain Kc=–0.5 and integral time constant tI=0.3 [min], stable and fast response with Integral Absolute Error (IAE) near to zero (0,0022) could be achieved.